Stock Market Responses to Macroeconomic Dynamics - Dil Krishna Shahu (Journal of Business and Social Sciences, 2023)
This study aims at examining how the stock market reacts to macro-economic dynamics. Using the annual data set of 28 years from 1995 to 2022, the study employed the OLS Regression model. Macroeconomic variables like Inflation rate, Interest rate, Exchange rate, and Gross Domestic Product were used in this study. The findings suggest that the Nepal stock market is significantly affected by gross domestic product and exchange rate whereas interest is insignificantly negative Nepal stock market. Understanding the way macroeconomic factors affect NEPSE can assist evaluate the state of the economy as a whole and its capacity to provide wealth and prosperity for both venture capitalists and the wide-ranging community.